History of Lesya Ukrainka’s Text: “Poet During the Siege” (Linguostylistic Studies, 2020)
The article is the sequel of the author's publications about the linguistic textologies of Lesya Ukrainka's poetry. Theoretical research is based on the analysis of different text options, which allows revealing the stages of the author's hard work while creating the final variant of a text. The research results contribute to a better understanding of the author's attitudes to the basics of versification, which she regarded as a prerequisite for poetic skill. The article attempts to trace the way of the poetic text creation, from the autograph to the last lifetime publication in the collection.A case study is the poem "Poet during the siege" – from the draft to the last publication. The goal of the study is to identify and analyze alterations at the semantic and formal levels.Lesia Ukrainka attached great importance to the formal organization of the text, and it is evidenced by the crossed along and across rough copies of her works. The writer painfully perceived the interference of editors in the form of her poetic works, and, therefore, she tried to bring them to perfection in form and sounding. The stylistic aspect of the text development to the fictional optimum is also topical.All editings of the poem are very important. They illustrate the author's poetic mastery evolution and expose significant moments of her creative thinking development.
Keywords: metre; autograph; variant; poetic text; stanza; emphasis; versification